Rethinking Breast Cancer Chemoprevention: Technological Advantages and Enhanced Performance of a Nanoethosomal-Based Hydrogel for Topical Administration of Fenretinide - Apolinário, Alexsandra Conceição; Salata, Giovanna Cassone; de Souza, Marcelo Medina; Chorilli, Marlus [UNESP]; Lopes, Luciana Biagini (Springer Nature, 2022)
Herein, we developed an ethosomal hydrogel based on three types of ethosomes: simple, mixed (surfactant-based micelles and lipid vesicles) or binary (comprising two type of alcohols). Ethanol injection was employed for vesicles preparation, and sodium alginate, as gelling agent. We purposed the local-transdermal administration of the off-the-shelf retinoid fenretinide (FENR) for chemoprevention of breast cancer. Rheograms and flow index values for alginate dispersion (without ethosomes) and hydrogels containing simple, mixed or binary ethosomes suggested pseudoplastic behavior. An increase in the apparent viscosity was observed upon ethosome incorporation. The ethosomal hydrogel displayed increased bioadhesion compared to the alginate dispersion, suggesting that the lipid vesicles contribute to the gelling and bioadhesion processes. In the Hen’s Egg Test–Chorioallantoic Membrane model, few spots of lysis and hemorrhage were observed for formulations containing simple (score of 2) and mixed vesicles (score 4), but not for the hydrogel based on the binary system, indicating its lower irritation potential. The binary ethosomal hydrogel provided a slower FENR in vitro release and delivered 2.6-fold less drug into viable skin layers compared to the ethosome dispersion, supporting the ability of the gel matrix to slow down drug release. The ethosomal hydrogel decreased by ~ five-fold the IC50 values of FENR in MCF-7 cells. In conclusion, binary ethosomal gels presented technological advantages, provided sustained drug release and skin penetration, and did not preclude drug cytotoxic effects, supporting their potential applicability as topical chemopreventive systems.
Keywords: Bioadhesion; Nanomedicine; Retinoid; Transdermal hydrogel